CROWN DIAMETER, CHILLING, AND GIBBERELLIC ACID INTERACTIONS INFLUENCE GROWTH AND REPRODUCTIVE OF STRAWBERRY CV. FESTIVAL. - Khalil, N. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
An experiment was conducted in unheated greenhouse units of the Department of Horticulture and Landscape -College of Agriculture- University of Baghdad on the first of October,   to observe the effects of amony interaction of crown diameter, chilling,  and foliar application of gibberellic acid on vegetative growth, and reproductive in cv. ‘Festival’ of strawberry (Fragaria x ananassa (Duch)). Using randomized Complete Block Design (RCBD), Plants were sorted into two groups according to crown diameter (11-15mm (Cd1)  and  6-10 mm (Cd2)), each of them sorted into two groups [Ch0 (without cold storage) and Ch1 (kept in a cold storage for  three weeks at 1-2°C), gibberellic acid was sprayed on plants, with concentration treatments included a control (G0) (distilled water), 150 mg. L–1 (G1) and 300 mg. L–1 (G2).The results showed the highest leaf number and Leaf area. Plant-1, (26.33), (29.70 dcm2) in (Cd1.Ch1.GA0) and (Cd1.Ch1. GA1) respectively, Number of stolon increased significantly by GAs application, the highest number were (8.3) in (Cd1.Ch1. GA2). The highest value of the TSS % was produced from the plants under the effect of  the treatment (Cd1.Ch1. GA0) (8.5%) and the highest pH were 3.70 from the treatment (Cd2.Ch0.GA2). The results indicated the superiority of treatment (Cd1.Ch0.GA0)     in fruit number (22.4), weight (17.77g) and a plant yield (398.2g).